PEMODELAN TAX AVOIDANCE BERDASARKAN KOMISARIS INDEPENDEN, LEVERAGE, DAN KOMITE AUDIT - Amelia, Weninda Rizky; Tohari, Amin; Kurniawan, Andy (Universitas Nusantara PGRI Kediri, 2023)
The purpose of this study was to determine the effect of independent commissioners, leverage, and audit committees on tax evasion either partially or simultaneously in automotive companies listed on the Indonesia Stock Exchange. This study uses a quantitative approach with ex post facto methods. The sample used in this study included 16 automotive companies and was analyzed using multiple linear regression with SPSS version 21 software. The conclusions of the result of this study were; (1) the independent commissioner variable [artially has no significant effect on tax avoidance in automotive sector companies listed on the IDX for the 2020-2022 period. (2) The leverage variable partially has no significant effect on tax evasion in automotive sector companies listed on the IDX for the 2020-2022 period. (3) The audit committee variable partially influences tax evasion in automotive sector companies listed on the IDX for the 2020-2022 period. (4) The independent commissioner, leverage, and audot committee variables simultaneously influence tax avoidance in automotive sector companies listed on IDX for the 2020-2022.